Combination of microRNA-21 and microRNA-146a Attenuates Cardiac Dysfunction and Apoptosis During Acute Myocardial Infarction in Mice - Wei Huang; Shan-Shan Tian; Peng-Zhou Hang; Chuan Sun; Jing Guo; Zhi-Min Du (Elsevier, 2016)
Recent studies have revealed the cytoprotective roles of microRNAs (miRNAs) miR-21 and miR-146a against ischemic cardiac injuries. While these studies investigated each of these miRNAs as an independent individual factor, our previous study has suggested the possible interaction between these two miRNAs. The present study was designed to investigate this possibility by evaluating the effects of miR-21 and miR-146a combination on cardiac ischemic injuries and the underlying mechanisms. MiR-21 and miR-146a synergistically decreased apoptosis under ischemia/hypoxic conditions in cardiomyocytes compared with either miR-21 or miR-146a alone. Mice coinjected with agomiR-21 and agomiR-146a had decreased infarct size, increased ejection fraction (EF), and fractional shortening (FS). These effects were greater than those induced by either of the two agomiRs. Furthermore, greater decreases in p38 mitogen-associated protein kinase phosphorylation (p-p38 MAPK) were observed with miR-21: miR-146a combination as compared to application of either of the miRNAs. These data suggest that combination of miR-21 and miR-146a has a greater protective effect against cardiac ischemia/hypoxia-induced apoptosis as compared to these miRNAs applied individually. This synergistic action is mediated by enhanced potency of inhibition of cardiomyocyte apoptosis by the miR-21'PTEN/AKT'p-p38'caspase-3 and miR-146a'TRAF6'p-p38'caspase-3 signal pathways.